2013
DOI: 10.4085/1062-6050-48.3.21
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Aspects of Athletic Injuries as Perceived by Athletic Trainers

Abstract: Context: Despite the Psychosocial Strategies and Referral content area, athletic trainers (ATs) generally lack confidence in their ability to use this information. Objective: The current study's primary purpose was to determine (a) perceived psychological responses and coping behaviors athletes may present to ATs, (b) psychosocial strategies ATs currently use with their athletes, (c) psychosocial strategies ATs deem important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
64
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 31 publications
1
64
0
3
Order By: Relevance
“…Thus, SMPs should consider an approach in which they are actively engaged in dialogues regarding the physical processes of injury, while being attuned to the possible psychosocial processes of injuries, such as cognitive and emotional reactions and barriers that may undermine the rehabilitation process. 8,17,50 Based on our results, we feel there are several points of note. First, the athletes reported their SMPs set targets for them throughout their rehabilitation and that they found this practice beneficial.…”
Section: Sport Medicine Professional As the Primary Treatment Providermentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, SMPs should consider an approach in which they are actively engaged in dialogues regarding the physical processes of injury, while being attuned to the possible psychosocial processes of injuries, such as cognitive and emotional reactions and barriers that may undermine the rehabilitation process. 8,17,50 Based on our results, we feel there are several points of note. First, the athletes reported their SMPs set targets for them throughout their rehabilitation and that they found this practice beneficial.…”
Section: Sport Medicine Professional As the Primary Treatment Providermentioning
confidence: 99%
“…16 Other investigations of SMPs' views yielded similar findings. For example, 99.7% of sport medicine physiotherapists surveyed in the United Kingdom 8 and 74.4% of the US athletic trainers 17 surveyed believed that, to some extent, all athletes are psychosocially affected by their injuries. 8 In both studies, the key strategies used with athletes were creating variety in rehabilitation exercises and short-term goal setting.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, evidence collected from ATs indicates that they appear to recognize the prevalence of psychosocial responses to athletic injuries, but their lack of education on how to appropriately deal with these responses limits their ability to properly incorporate athletes' reactions into their treatment plans and thereby provide holistic care. 2 Recently Kamphoff et al 3 suggested a variation of the phase-like approach to rehabilitation by integrating psychosocial components with physical characteristics of the healing process: reaction to injury, reaction to rehabilitation, and reaction to return to sport. 3 The development of these phases, guided by the physical healing process, has the potential to increase ATs' ability to provide holistic care to injured athletes.…”
mentioning
confidence: 99%